A Case Report of a Metastatic Gastrointestinal Stromal Tumor Occurring in Femur - Chang-kun Zheng; Wu-Sheng Kan; Peng Li (Case Reports in Gastrointestinal Medicine)
Gastrointestinal stromal tumors (GISTs) are mesenchymal neoplasms that most commonly affect the stomach or small intestine, but can occur anywhere throughout the gastrointestinal tract. To the best of our knowledge, few cases have been reported in the literature about the femur metastasis of GIST. This paper describes a metastasis of a gastrointestinal stromal tumour (GIST) to the femur in a 62-year-old male, 2 years after treatment for a gastric primary. There were no signs of tumor recurrence at followup after 12 mo. This case suggests that the femur can be a potential metastatic site of GIST.